Contemporary Fiqh Study: South Korea as a Country of Appearance-Oriented Views (외모 지상 주의) on Trend of Cosmetic Plastic Surgery - Muhamad Parhan; Mohammad Rindu Fajar Islamy; Ilham Kurnia Gustavakuan; Rizka Ade Purnama; Shakylla Putri Ragiel Utami (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
This research attempted to find out the view of Islamic law in modern fiqh studies on plastic surgery and Appearance oriented views (Lookism) in South Korea. The use of juridical empirical method, or also known as sociological research, aimed to provide an overview of the implementation of plastic surgery in society based on applicable law by analyzing problems in society through secondary data.According to the data from the International Society of Aesthetic Plastic Surgery (ISAPS) in 2019, South Korea was in fifth position as a country that is estimated to carry out the most plastic surgery procedures in the world, 2,571 times (5.1%). This shows that this country has an Appearance-oriented view (Lookism) which is part of the Lookism culture. According to Bio Med Central 2017 data, there was a high ratio of recurrent discrimination rates (OR: 3.70; 95% CI: 2.19-6.27) and ‘incident’ (OR: 3.10; 95% CI: 2.99-4.83) from 2005 to 2013 against individuals in the age group of 15-24 years.